European model of government: towards a patchwork with missing pieces - Ziller, Jacques (2001)
Among EU Member States, there are basically two models of government. The standard European model, mainly developed in Prussia and France at the beginning of the nineteenth-century, has been successfully imitated to a very large extent in combination with the adoption of a parliamentary regime. The British civil service adopted the same type of hierarchical organisation as it was particularly suitable to the Westminster model of government responsibility. Opposed to this standard European model, the Swedish model has long been seen as a survival of Ancient Regime administrations. In the last part of the twentieth-century, several institutions have been directly or indirectly imported from Sweden to other countries, without taking account of the environment which made them successful in their country of origin. Some of these institutions can be seen as a way to modernisation although they were established two centuries ago. Both models feature a small number of elements, which are closely interlinked and make the system work. They are based on entirely different systems of accountability. This article presents and compares those two models in order to allow a better understanding of recent reforms and their prospects of success or failure. - Reproduced
Keywords: European union